Development of gait assistive clothing-typed soft wearable robot for elderly adults - Koo, Sumin Helen; Lee, Young Bin; Kim, Changhwan; Kim, Gibaek; Lee, Giuk; Koh, Je Sung (International Journal of Clothing Science and Technology, 2020)
Purpose: The purpose of this research was to develop clothing-typed soft wearable robot embedded with textile-based actuators on ankles for elderly adults needing gait assistance. Design/methodology/approach: Design guidelines were developed and they included function (type, targeting area, routing line and anchor points), design (size/fit, fabric/material, fastener, detail, color) and actuator (shape memory alloy type, size, deformation type, integration material, integration technique and evaluation method). Fabric-based actuator, integration methods to fabrics, routing lines and anchoring points were developed based on the guidelines and evaluated. Then, three long socks types and a pants type were designed and prototyped. Routing line position displacement measurement test was conducted with the prototypes. A survey was conducted to investigate satisfaction, likeness and use intention on the design/prototype to modify the designs. Findings: Important design factors were identified, and design guidelines for clothing-typed soft wearable robots (SWRs) were developed. People satisfied the developed SWR designs and prototypes with mean scores over 4.60. Originality/value: The results are expected to be helpful for designers and developers of SWRs in the development process, and they will ultimately be beneficial to members of the elderly population who have gait difficulties.
Keywords: Design/methodology/approach; Development process; Elderly adults; Elderly populations; Integration method; Integration techniques; Use intentions; Wearable robots; Clothing-typed robot; Elderly adults; Gait assistance; Wearable robot